SPECTRAL STUDIES OF INTERACTION OF MESO-TETRA-(4N-ALLYLPYRIDYL)PORPHYRINS WITH poly(rG)poly(rC), poly(rI)poly(rC) AND poly(rA)poly(rU) - Ghazaryan, A. A.; Dalyan, Ye. B.; Haroutiunian, S. G.; Chalikian, T. V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
The interaction of TAlPyP(4) and AgTAlPyP(4) with poly(rG)poly(rC), poly(rI)poly(rC) and poly(rA)poly(rU) was studied by the CD and fluorescence spectral changes. Nonmetalloporphyrins bind to poly(rG)poly(rC) with two modes, preferring the intercalation to the external mode. They bind to poly(rA)poly(rU) preferentially in an outside manner and bind to poly(rI)poly(rC) in two types of binding modes. In contrast Ag-containing metalloporphyrin bind with the studied RNAs via outside mode. By the intensity of the interaction with porphyrins the studied RNAs can be placed in the following order: poly(rI)poly(rC)>poly(rA)poly(rU)>poly(rG)poly(rC).